PENINGKATAN KEMAMPUAN MENULIS TEKS DESKRIPSI MELALUI MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Nuril Mala, Silvia; Siska Mega Diana; Nindy Profithasari; Frida Destini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low ability to write descriptive texts among fifth-grade students at SD Negeri 6 Metro Timur serves as the background for this research. This study aims to analyze the improvement in descriptive text writing skills thru the Cooperative Integrated Reading and Composition (CIRC) learning model among elementary school students. The research uses a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consisted of 40 students determined thru a saturated sampling technique. Data were collected thru descriptive text writing tests, observations, and documentation. Data analysis was conducted thru prerequisite tests such as normality and homogeneity tests, as well as hypothesis testing using simple linear regression. The research results show that the application of the CIRC learning model has a significant impact on improving the ability to write descriptive texts among fifth-grade elementary school students.